Eksplorasi Program Ruang pada Rumah Aman Korban Kekerasan Wanita dan Anak berdasarkan Studi Kasus - Erisa; Abdullah Hibrawan (Jurnal Teknologi dan Desain, 2026)
Violence against women and children is a complex social issue that continues to occur across various contexts of space and time, requiring responses that are not only social but also spatial. Safe houses, as protective facilities, play a strategic role in supporting the recovery process of victims; however, existing spatial programming often fails to fully accommodate psychological needs, a sense of safety, and trauma-informed healing processes. This study aims to explore and analyze the spatial programming requirements of safe houses for women and child victims of violence based on case studies. The research employs a qualitative descriptive-exploratory approach through the analysis and comparison of relevant precedents, focusing on identifying spatial needs, spatial relationships, and environmental qualities that support recovery. The findings indicate that effective spatial programming should incorporate clear zoning between private, semi-private, and public areas, while integrating essential spaces such as counseling rooms, children’s play areas, communal spaces, and restorative open spaces. In addition, layered security, privacy, flexibility, and trauma-informed design approaches emerge as key factors in creating an environment that facilitates healing and enhances the sense of safety for victims.